Karakteristik fisikokimia dan antibakteri losion pembersih tangan yang dibuat dari rumput laut cokelat (Scytosiphon lomentaria): Karakteristik fisikokimia dan antibakteri losion pembersih tangan yang dibuat dari rumput laut cokelat (Scytosiphon lomentaria) - Lailatussifa, Radipta; Trowulan, Endang; Suhono, Lego; Sutrisno, Sutrisno (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Effective hand hygiene remains essential for reducing the transmission of foodborne and contact pathogens in daily life and in food handling contexts. Scytosiphon lomentaria seaweed has antimicrobial activity that can be applied as a hand sanitizer. This study aimed to determine the best addition of S. lomentaria to hand sanitizers, based on microbial inhibition and its characteristics. Lotion consisted of four treatments: 0 (control), 20, 30, and 40% S. lomentaria. The results showed that S. lomentaria powder contained bioactive polyphenol compounds with a total phenolic content of 117.70±1.40 mg GAE / g dry weight and an IC50 value of 455 ± 3.4 ppm, while lotion with the addition of S. lomentaria contained polyphenols and saponins. The best treatment was shown by S. lomentaria 40% hand sanitizer lotion with E. coli inhibition of 6.30±0.64 mm, S. aureus 6.85±1.12 mm, hedonic test of color, texture and absorption with a level of like to very like, neutral pH, greenish white color, O/W emulsion type, high adhesive power, homogeneous, and easily absorbed by the skin. This study can serve as an alternative reference for making lotions that provide adequate and safe antimicrobial activity for routine hygiene before eating and food handling.